2003
DOI: 10.1159/000072797
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Seeking Inpatient Cocaine Abusers Show Hypothalamic Dysregulation of Both Basal Prolactin and Cortisol Secretion

Abstract: Cocaine causes neuroendocrine aberrations in cocaine abusers with pituitary stress hormone secretion providing a window to the stress system in the brain. Substance abusers and control participants were hormonally profiled for 3 weeks. Abusers showed significant basal elevations in prolactin in week 1 with normalization over the 3 weeks. No differences in prolactin secretion were seen with either thyrotropin-releasing hormone stimulation or L-dopa suppression testing. Basal afternoon cortisol secretion was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
5
31
1
2
Order By: Relevance
“…Therefore, our present finding is consistent with and extends reports from other laboratories, demonstrating persistent HPA axis activation, with much longer duration after the cessation of chronic EDC. In addition, our result here is in agreement with several clinical reports showing higher basal plasma ACTH and cortisol levels in cocaine addicts after several weeks' cessation of cocaine selfadministration (Elman et al, 1999;Buydens-Branchey et al, 2002;Contoreggi et al, 2003;Wilkins et al, 2005;Fox et al, 2009). …”
Section: Hpa Hormonessupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, our present finding is consistent with and extends reports from other laboratories, demonstrating persistent HPA axis activation, with much longer duration after the cessation of chronic EDC. In addition, our result here is in agreement with several clinical reports showing higher basal plasma ACTH and cortisol levels in cocaine addicts after several weeks' cessation of cocaine selfadministration (Elman et al, 1999;Buydens-Branchey et al, 2002;Contoreggi et al, 2003;Wilkins et al, 2005;Fox et al, 2009). …”
Section: Hpa Hormonessupporting
confidence: 93%
“…Higher basal plasma ACTH and cortisol levels have been reported in cocaine addicts 1 day after the cessation of cocaine self-administration (Vescovi et al, 1992). In cocaine addicts with depressive symptoms, basal plasma cortisol levels are increased during early cocaine abstinence (Elman et al, 1999;Buydens-Branchey et al, 2002), an effect that may persist weeks and even months during abstinence (Contoreggi et al, 2003;Wilkins et al, 2005). However, other clinical studies have reported that after a brief period of abstinence, basal and corticotropin-releasing factor (CRF)-stimulated ACTH and cortisol levels in cocaine-dependent patients do not differ from those of healthy subjects (Mendelson et al, 1998;Jacobsen et al, 2001;Aouizerate et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this possibility, we observed a significant inverse correlation between basal CORT levels and the magnitude of the CORT response from baseline. Notably, it does not appear that human cocaine addicts experience similar reductions in HPA function, since basal cortisol and/or ACTH levels are reportedly unchanged (Mendelson et al, 1988) or elevated (Vescovi et al, 1992;Buydens-Branchey et al, 2002;Contoreggi et al, 2003) during withdrawal. This disparity between our preclinical findings and the clinical data suggests that either there are subtle differences in the effects of cocaine SA on the HPA axis between rats and humans or that our protocol does not precisely simulate the human condition, thus highlighting that, although the long-access SA approach may be useful for investigating certain aspects of cocaine addiction, it is by no means a complete model.…”
Section: Basal Cort Levelsmentioning
confidence: 99%
“…With repeated cocaine administration, adaptive changes in the HPA axis emerge and can be observed as disrupted basal HPA function during drug withdrawal in cocaine-dependent individuals (Vescovi et al, 1992;Buydens-Branchey et al, 2002;Contoreggi et al, 2003) and in rats (Sarnyai et al, 1998;Zorilla et al, 2001;Zhou et al, 2003). Less is known about how the response of the HPA axis to stressors is altered as a consequence of prior cocaine use.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to opiate use, cocaine administration results in enhanced HPA activity in both humans [23] and non-human primate species [24] . Interestingly, male monkeys have a more robust HPA response to cocaine use compared to females [24] however in rats, females exhibit a greater HPA response to cocaine than males.…”
Section: Adrenal Dysfunction In Drug Usementioning
confidence: 99%